2019
DOI: 10.1002/cjp2.153
|View full text |Cite
|
Sign up to set email alerts
|

External quality assessment demonstrates that PD‐L1 22C3 and SP263 assays are systematically different

Abstract: PD-L1 inhibitors are part of first line treatment options for patients with advanced non-small cell lung cancer. PD-L1 immunohistochemistry (IHC) assays act as either a companion or a complementary diagnostic. The purpose of this study is to describe the experience of external quality assurance (EQA) provider UK NEQAS ICC and ISH with the comparison of different PD-L1 assays used in daily practice. Three EQA rounds (pilot, run A and run B) were carried out using formalin fixed paraffin embedded samples with sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…Additional research into the different validation practices of the participants might provide a better insight as to why LDTs are currently underperforming. Some previous studies confirm our results, in which fewer LDTs passed the quality control compared with the clinically validated assays for PD-L1 [17,[27][28][29], and for ALK receptor tyrosine kinase IHC [35,36]. However, other studies reported a high concordance of LDTs with reference assays [21,37].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additional research into the different validation practices of the participants might provide a better insight as to why LDTs are currently underperforming. Some previous studies confirm our results, in which fewer LDTs passed the quality control compared with the clinically validated assays for PD-L1 [17,[27][28][29], and for ALK receptor tyrosine kinase IHC [35,36]. However, other studies reported a high concordance of LDTs with reference assays [21,37].…”
Section: Discussionsupporting
confidence: 88%
“…Irrespective of the protocol used, laboratories are required to appropriately verify or validate their PD-L1 IHC test, to take part in continuous quality monitoring and participation to External Quality Assessment (EQA) [24][25][26]. Lower staining concordance for LDTs compared with CE-IVD approved assays was reported by two other EQA providers [27][28][29], but participants' interpretation of the TPS was not always assessed [27]. The aim of this study is to evaluate the results of assessment of the staining concordance of PD-L1 IHC and its influence on TPS estimations, for the different (LDT or CDx approved) methods in two subsequent EQA schemes of the European Society of Pathology (ESP).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate measurement and scoring of PD-L1 protein expression is difficult due to various technical and biological pitfalls (Topalian, Taube, Anders, & Pardoll, 2016), and the choice of immunohistochemical assays and scoring strategies could lead to discrepancies between different studies (Dodson et al, 2019;Lenouvel et al, 2019). Several PD-L1 diagnostic assays are commercially available, such as Ventana SP263 (durvalumab), Dako 22C3 (pembrolizumab), and Dako 28-8 (nivolumab).…”
mentioning
confidence: 99%
“…In contrast, a meta-analysis of diagnostic accuracy of PD-L1 IHC assays concluded that properly designed LDTs may in fact achieve higher accuracy than commercial PD-L1 assays, when both are compared to an appropriate reference standard [11]. Various other studies have shown substantial interlaboratory concordance of PD-L1 staining for several commercial PD-L1 assays [22,[39][40][41], while another study stated that equivalence of commercial PD-L1 assays at the 1% and 50% cutoff cannot be assumed [42]. Lastly, a study by Butter et al [43] showed a similar degree of interlaboratory concordance between laboratories using a 22C3 LDT and laboratories using the 22C3 pharmDx commercial assay (Agilent), but also concluded that interlaboratory variability of immunostaining contributes to discrepancies in PD-L1 positivity between centers.…”
Section: Discussionmentioning
confidence: 98%
“…This may not always be the case in all laboratories, which may suggest that use of commercial assays could also contribute to reduction of interlaboratory variability in PD-L1 positivity. Nevertheless, this remains uncertain, since even laboratories that use the same commercial assay can produce differences in PD-L1 staining results [38,43] and others have reported inequality of commercial assays at the 1% and 50% cutoff [42]. To help create more awareness among pathologists, results from individual laboratories in our study were sent back to these laboratories as feedback reports.…”
Section: Discussionmentioning
confidence: 99%